Canadian chronic myeloid leukemia outcomes post-transplant in the tyrosine kinase inhibitor era. (October 2018) - Savoie, Mary Lynn; Bence-Bruckler, Isabelle; Huebsch, Lothar B.; Lalancette, Marc; Hillis, Chris; Walker, Irwin; Lipton, Jeffrey H.; Forrest, Donna L.; Kim, Dennis (Dong Hwan)
Highlights: A 1.3 log reduction in BCR-ABL levels within 3 months post HCT is prognostic in TKI resistance or intolerance. HCT remains a potential cure for patients with CML resistant or intolerant of TKI therapy. Advanced phase disease remains a poor prognostic factor post HCT even in the TKI era. Abstract: The majority of patients with TKI failure respond to HCT. However, the relapse risk remains high. This study has evaluated transplant outcomes in 223 CML patients with TKI failure due to resistance (n = 132) or intolerance (n = 29), as well as those that were TKI naïve/responding with advanced disease (n = 35) or with chronic phase (CP, n = 27). We studied outcomes according to post-transplant BCR-ABL transcript level within 3 months. With respect to transplant outcomes according to the post-transplant BCR/ ABLtranscript level within 3 months, the group failing to achieve a 1.3 log reduction (n = 14, 12.4%) showed the highest relapse rate of 78.6% at 5 years, compared to 26.2% and 24.1% in the groups achieving 1.3–4.0 log reduction (n = 45, 39.8%), and ≥4.1 log reduction (n = 54, 47.8%) respectively (p < 0.001). Multivariate analysis confirmed that the group failing to achieve a 1.3 log reduction had a 2.3-fold higher risk of death and 6.6 times higher risk of relapse. Poor overall survival after HCT was associated with advanced disease at diagnosis, but not disease status prior to HCT. Of 61 patients who relapsed after HCT, 47 were treated with post-transplant TKI therapy; those receiving TKI after loss of MR2 or MMR showed higher rates of response and survival compared to those receiving TKI after hematologic relapse (p < 0.001). QPCR log reduction level within 3 months post transplantation is prognostic in this population.